ANALYSIS OF ISSUES OF LEGAL ACTION FOR VIOLATION OF AGREEMENTS WITH ATHLETES IN UZBEKISTAN AND FOREIGN COUNTRIES - Xamraqulov To’lqin Toxirjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Issues of liability arise if the athlete does not fulfill the rights and obligations in the sports contract. In this case, additional types of legal responsibility should not be included in the labor law for the employer’s responsibility in case of violation of the terms of the contract in case of non-fulfillment of rights and obligations in the field of sports, because the integration of additional measures in the Labor Code of the Republic of Uzbekistan will lead to an increase in the list of sanctions.